LEGISLATIVE AND DOCTRINAL DETERMINATION OF VICTIM STATUS IN THE CIS MEMBER STATES - Turaeva Dilnoza Rustambaevna (TADQIQOTLAR.UZ, 2025)
Annotation. The article analyzes the legislative and doctrinal definition of the status of a victim in the criminal proceedings of the CIS member states.